From fibres to adhesives: evolution of spider capture threads from web anchors by radical changes in silk gland function - Wolff, Jonas O; Ashley, Leah J; Schmitt, Clemens; Heu, Celine; Denkova, Denitza; Jani, Maitry; Řezáčová, Veronika; Blamires, Sean J; Gorb, Stanislav N; Garb, Jessica; Goodacre, Sara L; Řezáč, Milan (Journal of the Royal Society, Interface, 2024)
Spider webs that serve as snares are one of the most fascinating and abundant type of animal architectures. In many cases they include an adhesive coating of silk lines-so-called viscid silk-for prey capture. The evolutionary switch from silk secretions forming solid fibres to soft aqueous adhesives remains an open question in the understanding of spider silk evolution. Here we functionally and chemically characterized the secretions of two types of silk glands and their behavioural use in the cellar spider, Pholcus phalangioides. Both being derived from the same ancestral gland type that produces fibres with a solidifying glue coat, the two types produce respectively a quickly solidifying glue applied in thread anchorages and prey wraps, or a permanently tacky glue deployed in snares. We found that the latter is characterized by a high concentration of organic salts and reduced spidroin content, showing up a possible pathway for the evolution of viscid properties by hygroscopic-salt-mediated hydration of solidifying adhesives. Understanding the underlying molecular basis for such radical switches in material properties not only helps to better understand the evolutionary origins and versatility of ecologically impactful spider web architectures, but also informs the bioengineering of spider silk-based products with tailored properties.
Keywords: predátorské chování; adhesive; pavouci; Biological Evolution; spidroin; Predatory Behavior; Animals; Adhesives; convergence; Silk; piriform silk; hedvábí; adheziva; zvířata; viscid silk; biologická evoluce; Spiders; spider silk